Henry Kirke Bush-Brown papers - Bush-Brown, Henry Kirke, 1857-1935.
Typescript of unpublished biography of Bush-Brown's uncle, Henry Kirke Brown (1814-1886), also a sculptor; memorandum books, household accounts, photographs, sketches, engravings, genealogical charts, clippings, poems, and printed matter. Correspondents include William Cullen Bryant, James Buchanan, Alonzo Potter, and John Quincy Adams Ward, Brown's student assistant and eminent sculptor.
Sculptor.
Collection material in English.
Keywords: Brown, Henry Kirke, -- 1814-1886.; Bryant, William Cullen, -- 1794-1878 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Potter, Alonzo, -- 1800-1865 -- Correspondence; Ward, John Quincy Adams, -- 1830-1910 -- Correspondence; Brown family; Sculptors -- Biography; Sculptors